Reduction of Magnitude and Frequency of Vertical Strabismus through Vision Therapy. - Aslakson, Emily (Optometry & Visual Performance, 2017)
Background: Vertical strabismus tends to be a condition that many optometrists treat with spectacle prism only. They may even offer surgical correction, rather than attempting vision therapy. Even optometrists who are fairly comfortable with vision therapy may shy away from offering therapy to patients with this condition because they believe that it is too time intensive or just does not work. Oftentimes, this means that patients are unaware of the option of vision therapy, even though they may be motived and willing to undergo this treatment. Case Report: This case outlines a 21-year-old Caucasian female with an 18Δ high-frequency intermittent left hypertropia who underwent office-based therapy and had exceptional results, in the reduction of both the magnitude and the frequency of her vertical deviation. Conclusion: Office-based vision therapy is a viable and effective treatment method for patients with vertical strabismus. Patient motivation is critical to the effectiveness of the treatment. This case demonstrates the efficacy of intensive officebased vision therapy on a patient with vertical strabismus.